2022
DOI: 10.3390/pharmaceutics14101999
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of a Gastro-Resistant HPMC-Based “Next Generation Enteric” Capsule

Abstract: Many orally dosed APIs are bioavailable only when formulated as an enteric dosage form to protect them from the harsh environment of the stomach. However, an enteric formulation is often accompanied with a higher development effort in the first place and the potential degradation of fragile APIs during the coating process. Ready-to-use enteric hard capsules would be an easily available alternative to test and develop APIs in enteric formulations, while decreasing the time and cost of process development. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…This in combination with its robust nature made it straightforward to incorporate into both capsule shells and tablet dosage form types. This powerful feature was ideal for testing and developing gastroresistant capsules, ,, where disintegration of the capsule shell was delayed until it reached the intestine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This in combination with its robust nature made it straightforward to incorporate into both capsule shells and tablet dosage form types. This powerful feature was ideal for testing and developing gastroresistant capsules, ,, where disintegration of the capsule shell was delayed until it reached the intestine.…”
Section: Resultsmentioning
confidence: 99%
“…The use of magnetite was explored for the determination of the disintegration site and time for dosage forms, predominantly capsules. However, in several studies, ,,, problems determining exact disintegration site and time were reported due to the large size of the susceptibility feature of magnetite. This limitation was addressed by Grimm in a study where they made a clear distinction not to define a capsule rupture, but a process of “dispersion”, defined as the appearance of several small artifacts or a change in the size or the geometry of the artifact.…”
Section: Resultsmentioning
confidence: 99%
“…21,24,27,28,31,33 Reliable identification of drug delivery systems in MRI images requires either a unique signal or a combination of signals resulting in an identifiable signature. 15,16,19 In this study, we used ferrimagnetic black iron oxide (magnetite) as a tracer for the coated capsule because it produces a characteristic susceptibility artifact in the applied TRUFI sequence. In principle, other ferro-or ferrimagnetic substances, such as iron or nickel, could be used as well.…”
Section: Discussionmentioning
confidence: 99%
“…Once it is released from the capsule into the intestine, caffeine dissolves very quickly because of its high solubility and is rapidly absorbed, appearing in saliva almost immediately . Accordingly, the appearance of caffeine in saliva provides a sensitive measure of capsule disintegration. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation